1976
DOI: 10.1128/aem.31.6.931-935.1976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antimicrobial soap containing chlorhexidine on the microbial flora of skin

Abstract: The qualitative and semiquantitative changes in the aerobic microbial flora of normal skin with the prolonged use of a chlorhexidine scrub (6 months) were investigated. More samples in the chlorhexidine scrub group had gram-negative bacilli in their axilla (63 of 96, 66%) and groin (36 of 96, 38%) than the controls (32 of 66, 49%, for axilla and 7 of 66, 11%, for groin; P = 0.01). Klebsiella and Enterobacter were the predominant organisms in the control and chlorhexidine groups, respectively. The chlorhexidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Reduced incidence (23% down to 5%) of urinary tract infection has also been associated with use of chlorhexidine glycerol to lubricate the catheter (Miller, Linton, Slade, Gillespie, & Mitchell, 1960). However, chlorhexidine used for a prolonged time period (i.e., 6 months) has been associated with an overgrowth of gram-negative organisms, while maintaining staphylococci (Aly & Maibach, 1976).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Reduced incidence (23% down to 5%) of urinary tract infection has also been associated with use of chlorhexidine glycerol to lubricate the catheter (Miller, Linton, Slade, Gillespie, & Mitchell, 1960). However, chlorhexidine used for a prolonged time period (i.e., 6 months) has been associated with an overgrowth of gram-negative organisms, while maintaining staphylococci (Aly & Maibach, 1976).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Though many studies in the past few decades have sought to correlate handwashing frequency and agent used with the numbers and types of bacteria on the skin of the hands (Larson 1984, Aly & Maibach 1976, Casewell & Phillips 1977, Ojajarvi 1980), very little has been done to assess the quality or technique of handwashing as practised in clinical settings. Those few published studies that have reported the rating of handwashing technique have used observation tools for which validity and reliability data are unavailable (Fox et al.…”
Section: Introductionmentioning
confidence: 99%
“…Though many studies in the past few decades have sought to correlate handwashing frequency and agent used with the numbers and types of bacteria on the skin of the hands (Larson 1984, Aly & Maibach 1976, Casewell & Phillips 1977, Ojajarvi 1980, very little has been done to assess the quality or technique of handwashing as practised in clinical settings. Those few published studies that have reported the rating of handwashing technique have used observation tools for which validity and reliability data are unavailable (Fox et al 1974, Taylor 1978.…”
Section: Introductionmentioning
confidence: 99%